STRUCTURAL SYNTHESIS OF A STABILIZING ROBUST CONTROLLER OF THE ROTOR FLUX LINKAGE - N. J. Khlopenko (National Technical University "Kharkiv Polytechnic Institute", 2017)
Purpose. The aim is to structural synthesis of robust stabilizing control of the rotor flux vector control system of induction motor. Methodology. Synthesis controller structure was carried out in two stages. The first stage constructed a mathematical model of the channel of the rotor flux with parametric uncertainty and calculated transfer function of H∞-suboptimal controller by method of the mixed sensitivity. The second stage was carried out the expansion of the transfer function of the continued fraction for the Euclidean algorithm. This fraction was used to construct the controller structural scheme. Results. Computer modeling of the transfer function of H∞-suboptimal controller. Achieved decomposition found the transfer function of the continued fraction. The flow diagram of suboptimal H∞-controller with a proportional and integrating links and a few summers. The curves of transient rotor flux linkage in packages Robust Control Toolbox and Simulink. They coincide in the steady state, but differ among themselves in the transition. Originality. We developed the method of structural synthesis of robust stabilizing controller of the flux linkage rotor, H∞-suboptimal structural scheme of which is presented in the form of simple compounds integrating and proportional elements of the same order as the controller with the strictly correct transfer function, and takes into account the parametric uncertainty of control object. The results of the simulation of transient processes in a variety of packages MATLAB applications confirms the adequacy and small sensitivity of the system to parametric perturbation. Practical value. The resulting structure of the controller makes it possible to carry out the modernization of electric control systems, in use, with minimal financial costs.